Transcatheter aortic valve implantation for aortic stenosis in high surgical risk patients: A systematic review and meta-analysis. - Zulian Liu; Elaine Kidney; Danai Bem; George Bramley; Susan Bayliss; Mark A de Belder; Carole Cummins; Rui Duarte (PLoS ONE, 2018)
Background Symptomatic aortic stenosis has a poor prognosis. Many patients are considered inoperable or at high surgical risk for surgical aortic valve replacement (SAVR), reflecting their age, comorbidities and frailty. The clinical effectiveness and safety of TAVI have not been reviewed systematically for these high levels of surgical risk. This systematic review compares mortality and other important clinical outcomes up to 5 years post treatment following TAVI or other treatment in these risk groups. Methods A systematic review protocol was registered on the PROSPERO database (CRD42016048396). The Cochrane Library, Centre for Reviews and Dissemination Databases, MEDLINE, EMBASE, and ZETOC were searched from January 2002 to August 2016. Clinical trials or matched studies comparing TAVI with other treatments for AS in patients surgically inoperable or operable at a high risk were included. Data extraction and quality assessment were conducted by two reviewers. Data were pooled using random-effects meta-analysis. The main outcomes were all-cause mortality, efficacy and major complications. Results Three good quality randomised controlled trials (RCTs) were included. Patients' mean age ranged from 83-85 years, around half were female and New York Heart Association (NYHA) functional class III or IV ranged from 83.8% to 94.2% with frequent comorbidities. In 358 surgically inoperable patients from one RCT, TAVI was superior to medical therapy for all-cause mortality at 1 year (hazard ratio (HR) 0.58, 95% confidence interval (CI) 0.36-0.92), 2 years (HR 0.50, 95% CI 0.39-0.65), 3 years (HR 0.53, 95% CI 0.41to 0.68) and 5 years (HR 0.50, 95% CI 0.39-0.65), and NYHA class III or IV at 2 years (TAVI 16.8% (16/95), medical therapy 57.5% (23/40), p<0.001), quality of life and re-hospitalisation. TAVI had higher risks of major bleeding up to 1 year, of stroke up to 3 years (at one year 11.2% versus 5.5%, p = .06; HR at 2 years 2.79, 95% CI 1.25-6.22; HR at 3 years 2.81; 95% CI 1.26-6.26) and of major vascular complication at 3 years (HR 8.27, 95% CI 2.92-23.44). Using the GRADE tool, this evidence was considered to be of moderate quality. In a meta-analysis including 1,494 high risk surgically operable patients from two non-inferiority RCTs TAVI showed no significant differences from SAVR in all-cause mortality at two years (HR 1.03, 95% CI 0.82-1.29) and up to 5 years (HR 0.83, 95% CI 0.83-1.12). There were no statistically significant differences in major vascular complications and myocardial infarction at any time point, discrepant results for major bleeding on variable definitions and no differences in stroke rate at any time point. Using the GRADE tool, this evidence was considered of low quality. Conclusions Symptomatic aortic stenosis can be lethal without intervention but surgical resection is contraindicated for some patients and high risk for others. We found that all-cause mortality up to 5 years of follow-up did not differ significantly between TAVI and SAVR in patients surgically operable at a high risk, but favoured TAVI over medical therapy in patients surgically inoperable. TAVI is a viable life-extending treatment option in these surgical high risk groups.